An appraisal of the arithmetic competencies of the elementary school teachers in the district of Bago, Negros Occidental - Orleans, Leonardo P. 1924- (s.n.], 1966)
This study determines the adequacy of the arithmetic competencies of the teachers in Bago, Negros Occidental. Certain factors that seem to relate to the acquisition of these competencies were also investigated.